Generation and therapeutic evaluation of recombinant immunotherapeutics on CD64+ monocytic cell lines and polarized ex vivo differentiated human macrophages - Fajemisin, Emmanuel Adebowale (Department of Integrative Biomedical Sciences (IBMS), 2025)
Introduction: Dysfunctional monocytes/macrophages have been associated with the initiation and maintenance of several chronic diseases such as rheumatoid arthritis (RA), cancer, atopic dermatitis (AD), leishmaniasis etc. In RA for example, the imbalance between pro-inflammatory and anti-inflammatory macrophages has been linked to the chronicity and prolonged inflammation observed in RA. In other diseases like cancers, tumor-associated macrophages (TAMs) form the bulk of the tumor mass and help support tumor growth and metastasis. Also, naïve macrophages can be infiltrated by pathogens and become active reservoirs of parasites like viruses, and protozoans as observed in some diseases like cutaneous leishmaniasis. Unfortunately, there are currently no clinically approved therapeutics to selectively eliminate disease-causing macrophages. In this regard, this thesis aimed to generate and evaluate the potential of different therapeutic agents to selectively eliminate the population of dysfunctional macrophages/monocytes. Previous literature and research have identified Fc gamma receptor I (FcγRI)/CD64 as a significant therapeutic target. CD64 is a transmembrane surface receptor found exclusively in myeloid lineage cells such as monocytes and different macrophage subtypes. Hence, protein engineering and biotechnology techniques were used to develop CD64-targeting immunotherapeutics that could selectively target and deliver cytotoxic agents into the disease-causing monocytic / macrophage population. Methods: The CD64-targeting antibody fragment (H22(scFv)) was used to generate; 1) a recombinant immunotoxin (rIT) through genetic fusion with the enzymatic domain of Pseudomonas aeruginosa exotoxin A (ETA`), or 2) a SNAP-tag fusion protein (FP) to allow chemical coupling of the antibody fragment to the cytostatic drug monomethyl auristatin F (AURIF) or the light sensitive dye IR700. By so doing generating an antibody drug conjugate (ADC) or a photoimmunoconjugate (PIC) respectively. Herewith, the therapeutics evaluated in this thesis are highlighted below: (1) rITs: H22(scFv)-ETA`, and its deimmunized version; H22(scFv)-dETA` (2) ADC: H22(scFv)-SNAP-AURIF (3) PIC: H22(scFv)-SNAP-IR700 Results and Discussion: All the anti-CD64 recombinant FPs were successfully expressed and characterized. After structural validation, full-length proteins were evaluated for their functional and biological activities in vitro. rITs – H22(scFv)-ETA`, and H22(scFv)-dETA`(RG7787-MT2), and SNAP FP, H22(scFv)-SNAP demonstrated significant antigen-specific binding to IFN-γ stimulated CD64-positive U937 and HL60 monocytic cells but not to antigen-negative cells. The functional (binding) activity of the anti-CD64 fusion proteins demonstrated by flow cytometry confirmed that the H22(scFv) antibody domain of each recombinant protein exhibited a properly folded conformation and maintained sufficient functional antigen-binding properties. Both H22(scFv)-ETA` and H22(scFv)-dETA`(RG7787-MT2) demonstrated dose-dependent cytotoxicity with IC50 values in the nanomolar range against IFN-γ stimulated antigen-positive monocytic cell lines U937 and HL60. In addition, the ADC; H22(scFv)-SNAP-AURIF showed a dose-dependent killing of both IFN-γ stimulated and unstimulated CD64+ proliferating cells but not on antigen-negative cells. This next-generation ADC offers clinical benefits over rITs due to its non-protein cytotoxic agent (AURIF) that is unaffected by endosomal proteases. Similarly, the PIC,H22(scFv)-SNAP-IR700 compromised cell viability in all ex vivo human monocyte-derived macrophage subtypes. Since this PIC is activated by near-infrared light, it gives more control over which tissue/area of tissue for selective targeting/elimination of the macrophage subpopulation implicated in the specified diseases. Also, IR700 is a photosensitizing dye which functions as a theranostic agent under visible light – offer the potential for dual clinical benefits in the diagnosis and therapy of topical chronic skin inflammatory diseases, skin cancers and solid cancers in a minimally invasive manner. Conclusion: CD64-targeting immunotherapeutics showed preliminary therapeutic potential and could serve as precision therapy for monocyte and macrophage-mediated diseases in the future.